(untitled) (Global Journal of Science Frontier Research, 2012)
An attempt has been made to establish an integral concerning the product of two H-function of several complex variables (Srivastava and Panda [8] with extended Jacobi polynomial [5]). Mainly we are using the series representation of H-function given by Olkha and Chaurasia [6,7]. By assigning suitable values to the parameters, the results can be reduced to many new, known and unknown results.